2018
DOI: 10.1111/jcmm.13546
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 deficiency decreases iron and haemoglobin through hepcidin up‐regulation by multilayer compensatory mechanisms

Abstract: To maintain iron homoeostasis, the iron regulatory hormone hepcidin is tightly controlled by BMP‐Smad signalling pathway, but the physiological role of Smad7 in hepcidin regulation remains elusive. We generated and characterized hepatocyte‐specific Smad7 knockout mice (Smad7 Alb/Alb), which showed decreased serum iron, tissue iron, haemoglobin concentration, up‐regulated hepcidin and increased phosphor‐Smad1/5/8 levels in both isolated primary hepatocytes and liver tissues. Increased levels of hepcidin lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Lastly, erythropoiesis has been theorised to reduce hepcidin expression acting through growth differentiation factor 15 (GDF-15), twisted gastrulation factor 1 (TWSG1) or erythroferrone (ERFE), however the exact mechanism is not understood. An et al demonstrated that phosphorylation of SMAD1/5/8 is regulated by the inhibitory SMADs 6 and 7 [24]. Hepatocyte-specific Smad7 knockout mice demonstrated a decrease in non-haem iron within the liver and spleen, in addition to decreases in L-ferritin and FPN levels [24].…”
Section: Hepcidin Regulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Lastly, erythropoiesis has been theorised to reduce hepcidin expression acting through growth differentiation factor 15 (GDF-15), twisted gastrulation factor 1 (TWSG1) or erythroferrone (ERFE), however the exact mechanism is not understood. An et al demonstrated that phosphorylation of SMAD1/5/8 is regulated by the inhibitory SMADs 6 and 7 [24]. Hepatocyte-specific Smad7 knockout mice demonstrated a decrease in non-haem iron within the liver and spleen, in addition to decreases in L-ferritin and FPN levels [24].…”
Section: Hepcidin Regulationmentioning
confidence: 99%
“…An et al demonstrated that phosphorylation of SMAD1/5/8 is regulated by the inhibitory SMADs 6 and 7 [24]. Hepatocyte-specific Smad7 knockout mice demonstrated a decrease in non-haem iron within the liver and spleen, in addition to decreases in L-ferritin and FPN levels [24]. Conversely, hepcidin and phosphorylated SMAD1/5/8 levels were increased in these mice [24].…”
Section: Hepcidin Regulationmentioning
confidence: 99%
See 3 more Smart Citations